PENGARUH TINGKAT KESULITAN KEUANGAN TERHADAP MANAJEMEN LABA: TEORI KEAGENAN VERSUS TEORI SIGNALING - Eko Widodo Lo (Jurnal Riset Akuntansi dan Keuangan, 2012)
This research investigates the influence of company financial distress on earnings management by using agency and signaling theories. This research compares the explanations between agency and signaling theories on this relationship. Agency theoryexplains that company financial distress positively influences earnings management, but signaling theory predicts that company financial distress negatively influences earningsmanagement. Company financial distress is measured by using Ohlson model. Kang- Sivaramakrishnan model is used to measure discretionary accruals, a measure of earningsmanagement. Empirical data are analyzed by using ordinary least square regression and testing of difference between two proportions from one group. Results of data analysis rejectagency theory explanation, and support signaling theory explanation. This research finds that company financial distress negatively influences discretionary accruals.Keywords: Financial distress, earnings management, agency theory, signaling theory